2022
DOI: 10.1111/echo.15367
|View full text |Cite
|
Sign up to set email alerts
|

Decreased fetal cardiac output in pregnant women with severe SARS‐Cov‐2 infection

Abstract: Aim:We aimed to examine fetal cardiac output (CO) in patients who recovered from severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2) infection. Materials:This prospective study included 48 pregnant women recovered from SARS-CoV-2 infection and 50 control cases. SARS-CoV-2 infection was diagnosed by polymerase chain reaction (PCR) test in patients. Fetal echocardiographic evaluations were performed at 24-37 weeks of gestation in pregnant women who recovered from the infection and control group. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…A prospective study conducted by Rizzo et al [ 68 ] on 54 infected and 108 non-infected pregnant women indicated no statistically important difference in umbilical vein blood flow/abdominal circumference (UVBF/AC) ( p = 0.07) in the left and right Atrial Area (AA) (left 1.30 vs. 1.28 p = 0.221 and right 1.33 vs. 1.31 p = 0.324), as well as in the ventricular sphericity indices (SI) (left 1.75 vs. 1.77 p = 0.208 and right 1.51 vs. 1.54 p = 0.121) between the two groups. Fetal cardiac output (CO) was evaluated in 48 pregnant women with severe COVID-19 and 50 controls by Turgut et al [ 69 ]. They demonstrated that fetal left CO dramatically decreased in women with severe disease after recovery compared to the controls (285.1 ± 114.7 vs. 246.7 ± 109.0 p = 0.058).…”
Section: Resultsmentioning
confidence: 99%
“…A prospective study conducted by Rizzo et al [ 68 ] on 54 infected and 108 non-infected pregnant women indicated no statistically important difference in umbilical vein blood flow/abdominal circumference (UVBF/AC) ( p = 0.07) in the left and right Atrial Area (AA) (left 1.30 vs. 1.28 p = 0.221 and right 1.33 vs. 1.31 p = 0.324), as well as in the ventricular sphericity indices (SI) (left 1.75 vs. 1.77 p = 0.208 and right 1.51 vs. 1.54 p = 0.121) between the two groups. Fetal cardiac output (CO) was evaluated in 48 pregnant women with severe COVID-19 and 50 controls by Turgut et al [ 69 ]. They demonstrated that fetal left CO dramatically decreased in women with severe disease after recovery compared to the controls (285.1 ± 114.7 vs. 246.7 ± 109.0 p = 0.058).…”
Section: Resultsmentioning
confidence: 99%
“…We attributed this result to the fact that SARS‐COV‐2 infection affects the fetoplacental and fetal circulation either by maternal hypoxia‐related fetal hypoxemia or by infection‐related inflammatory processes and so probably affects the fetal organs such as the fetal heart. Two studies from our center that evaluated the fetal cardiac effects of SARS‐COV‐2 in pregnant women who recovered from the infection concluded that fetal cardiac output was significantly decreased in pregnant women who recovered from severe infection, and therefore placental dysfunction and inflammation related to SARS‐COV‐2 infection might cause fetal cardiac changes 26,27 . These changes can be both functional, such as changes in cardiac output, or biochemical, such as changes in pro‐BNP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies from our center that evaluated the fetal cardiac effects of SARS-COV-2 in pregnant women who recovered from the infection concluded that fetal cardiac output was significantly decreased in pregnant women who recovered from severe infection, and therefore placental dysfunction and inflammation related to SARS-COV-2 infection might cause fetal cardiac changes. 26,27 These changes can be both functional, such as changes in cardiac output, or biochemical, such as changes in pro-BNP levels.…”
Section: Is Cord Pro-bnp Level Different In Newborns Born From Sars-c...mentioning
confidence: 99%
“…Fetal assessment of the CO is important as fetal well‐being is associated the cardiac functions. In recent studies, changes in CO have been demonstrated in diabetic mother fetuses, intrauterine growth restriction, and SARS‐Cov‐2‐infected mother fetuses 9–11 . However, the relationship between fetal cardiac function and maternal hypothyroidism, and levothyroxine replacement in pregnant women with hypothyroidism is unclear 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, changes in CO have been demonstrated in diabetic mother fetuses, intrauterine growth restriction, and SARS-Cov-2-infected mother fetuses. [9][10][11] However, the relationship between fetal cardiac function and maternal hypothyroidism, and levothyroxine replacement in pregnant women with hypothyroidism is unclear. 12,13 We hypothesized that hypothyroidism might affect fetoplacental circulation even though the F I G U R E 1 Left ventricular outflow tract (LVOT), the aortic valve velocity waveform.…”
Section: Introductionmentioning
confidence: 99%